Innovating portuguese traditional pastry – on the use of pasteurised egg yolk in “ovos moles” - Fundo, J. (2011)
“Ovos moles” is a renowned traditional Portuguese sweet that is confectioned with egg yolk, sugar and water. In this work a safer and easier to manipulate raw material - pasteurised liquid egg yolk - is proposed to substitute the intact shell eggs used in traditional “ovos moles” production. Due to previous heat treatment, pasteurised liquid egg yolk presents different sensorial, nutritional and physical properties. These changes may alter the final product’s characteristics. In order to develop a safer formulation, using pasteurised raw products, with minimised differences from the traditional product, a study on adding pasteurised egg white (as bulking agent) to the pasteurised liquid yolk was carried out. Samples made with normal shell eggs and with pasteurised liquid eggs were compared in terms of rheological parameters. Results allow characterising the physical properties of traditional ovos moles and of alternative formulations, using pasteurised egg yolk and white. A new formula, with rheological properties identical to the traditional one, was developed.